Sustainable development and gender well-being - Caren Grown; Maria Floro; Odera Onyechi (Environmental Research: Climate)
This paper examines the intersections between planetary boundary transgressions—specifically material footprint and CO _2 emissions—and gender disparities in human well-being. By extending the UN Development Programme’s Human Development Index, which measures a country’s achievements in health, education and income per capita, and Hickel’s Sustainable Development Index (SDI), which examines the ecological efficiency of human development, this study proposes a novel sex-disaggregated measure to assess the well-being of women and men after accounting for each country’s ecological impact across 151 countries. The empirical analysis reveals that countries that exceed ecological boundaries, notably through elevated CO _2 emissions and material footprints, often experience reduced levels of sustainable well-being, disproportionately impacting women due to existing disparities in education and income earnings. Gender differences in SDI outcomes reflect both ecological overshoot consequences and baseline gender inequalities in human development. Due to the paucity of sex-disaggregated data for all countries on the well-being effects that can be attributed to planetary boundary transgressions, the paper also examines whether or not ambient and household air pollution affects the mortality rates of women and men differently. The results may be useful for climate change modeling efforts and quantitative analysis that links the effects of climate change hazards to gender inequality, as well as for policymakers seeking to implement equitable climate policies.